Propriedades magnéticas e magnetoelétricas de compósitos multiferroicos de Pb[Zr0,53Ti0,47]O3/NixCo1-xFe2O4 - Dalla Costa, Leonardo José (2023)
New technologies are arising from the research and development of magnetism, especially those related to processing, information storage and sensors, are becoming increasingly important. in this regard, magnetoelectric multiferroic materials have been extensively tested for technological applications. Composite multiferroic materials are a combination of two materials with different ferroic orders, such as ferroelectricity and ferrimagnetism. In magnetoelectric compounds, magnetoelectricity is observed due to the mechanics between a piezoelectric material (ferroelectric phase), with a magnetostrictive material, such as ferrites. Ferrites can be made of different elements, like cobalt (CFO) and nickel (NFO), these two examples present opposite behavior in their coercive fields and decreasing values of remanent magnetization and saturation magnetization. Which results in different magnetostrictive responses. In this Ph.D. thesis we propose to study compounds of Pb[ZrₓTi₁₋ₓ]O₃ (PZT) with NixCo1-xFe2O4 ferrites (N/CFO) with 0≤x≤1, in the molar proportion of 80% PZT and 20% N /CFO with the aim of varying the magnetoelectric behavior of these compounds by varying the influence of modified Nickel or cobalt. The results obtained demonstrated that when synthesizing N/CFO ferrites it was possible to vary the effective anisotropy and, as a consequence, the magnetostrictive behavior of these ferrites. It should also be noted that the saturation magnetization of the compounds depends on the electrical polarization, being reduced by up to 15%, but without changing the coercivity, a drop that occurs due to the presence of a high electric field inside the composite can lead to a change in the valence of the ions of Faith. Magnetoelectric measurements as a function of the magnetic field frequency showed a change in the resonance frequency as a function of the Ni concentration of the ferrite. The results obtained indicate that the replacement of Co2+ by Ni2+ in ferrites structure have significantly alters the magnetoelectric properties of the investigated compounds.